Cell competition drives bronchiolization and pulmonary fibrosis - Rachel Warren; Kylie Klinkhammer; Handeng Lyu; Joseph Knopp; Tingting Yuan; Changfu Yao; Barry Stripp; Stijn P. De Langhe (Nature Communications)
Abstract Idiopathic pulmonary fibrosis (IPF) is a progressive respiratory scarring disease arising from the maladaptive differentiation of lung stem cells into bronchial epithelial cells rather than into alveolar type 1 (AT1) cells, which are responsible for gas exchange. Here, we report that healthy lungs maintain their stem cells through tonic Hippo and β-catenin signaling, which promote Yap/Taz degradation and allow for low-level expression of the Wnt target gene Myc. Inactivation of upstream activators of the Hippo pathway in lung stem cells inhibits this tonic β-catenin signaling and Myc expression and promotes their Taz-mediated differentiation into AT1 cells. Vice versa, increased Myc in collaboration with Yap promotes the differentiation of lung stem cells along the basal and myoepithelial-like lineages allowing them to invade and bronchiolize the lung parenchyma in a process reminiscent of submucosal gland development. Our findings indicate that stem cells exhibiting the highest Myc levels become supercompetitors that drive remodeling, whereas loser cells with lower Myc levels terminally differentiate into AT1 cells.